Spontaneous pregnancy after thread-embedding therapy treatment with premature ovarian insufficiency after unilateral oophorectomy: a case report - Zhang, Ziniu; Yuan, Jingxue; Zhao, Jingjing; Song, Yue; Ni, Jinxia (Frontiers in Medicine, 2024)
Premature ovarian insufficiency (POI) is a condition characterized by menstrual disturbance, subfertility, and estrogen deficiency symptoms. Women with POI have a small chance of natural conception, which may be even smaller when complicated with unilateral ovarian due to reduction of the ovarian follicular reserve. In China, acupuncture has been widely used to treat POI and POI-induced infertility, and studies have shown that acupuncture is helpful for improving ovarian function. Thread-embedding therapy is a method of acupuncture treatment development and extension, which can make the acupuncture effect last. In this article, we report a patient diagnosed with POI after unilateral oophorectomy (UO) who spontaneously conceived after thread-embedding therapy. Thread-embedding therapy may improve ovarian function in patients with POI, thereby providing a treatment strategy for infertility in patients with POI. This case report was written in accordance with the CARE guidelines.